Pengembangan Model Permainan Berbasis Outbound dalam Karakter Komunikatif Kelas 5 SD N 1 Klopoduwur - Sukma Eka Pratiwi; Asep Ardiyanto; Ferina Agustini (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
The background of this research is that the outbound-based game model has not been implemented in a maximally communicative character and the lack of communication between students and teachers, as well as students and students. This study aims to develop an outbound-based game model in terms of communicative character in the 5th grade students of SD N 1 Klopoduwur. The method used is the Research and Development method using two data analysis techniques, namely descriptive data analysis techniques and quantitative descriptive analysis. The results of the research show that the developed outbound-based game model can improve communicative character in the 5th grade students of SD N 1 Klopoduwur The outbound-based game model in communicative characters that has been developed meets valid criteria as a game model in communicative characters that have been adapted to indicators of communicative character, and has met the acceptance criteria as an outbound-based game model from teacher responses and student responses.So it can be concluded that Outbound-based game models can improve communicative character for students, are valid and appropriate for grade 5 students at SD N 1 Klopoduwur.